The implementation of selected elements of the CSR concept on the example of agribusiness enterprises from Warmia and Mazury = Implementacja wybranych elementów koncepcji CSR na przykładzie przedsiębiorstw agrobiznesu z Warmii i Mazur - Ratajczak, Marcin (Zielona Góra: Faculty of Economics and Management Press)
The concept of corporate social responsibility, functioning under the name of CSR (Corporate Social Responsibility), which is the responsibility of the business, is becoming more popular not only in academia, but also business. The purpose of this paper is to present the issues related to the implementation of selected elements of the concept of CSR (codes of ethics, norms and standards for quality management and dialogue with stakeholders) in the surveyed enterprises agribusiness.
Keywords: koncepcja CSR; agrobiznes; kodeksy etyczne; interesariusze; przedsiębiorstwo; CSR; agrobusiness; codes of ethics; stakeholders; enterprises